Pengembangan sistem pertanian bawang merah: uji daya hasil produksi true shallot seed - Susanto, Anang; Adinurani, Praptiningsih Gamawati; Wirayudha, Farhan (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: One of the leading horticultural commodities in Nganjuk District, East Java, with the highest production potential, is shallots. The study aimed to obtain a model that could be developed in Nganjuk District, East Java Province, in the shallot farming system. Methods: The research was conducted in lowland rice fields in Nganjuk District. The research involved three cooperative farmers with a land area of 1 hectare. This research provided treatments to four varieties of True Shallot Seed shallots, namely Bima Brebes, Trisula, and Lokananta. The treatments were then repeated four times. A randomized block design was used with data on plant growth, central pest and disease attacks, and yield components. The collected data were then processed and statistically analyzed using analysis of variance and further Duncan's Multiple Range Test (DMRT) and other tests at a 95% confidence level. Findings: Harvest results varied according to plant conditions and growth, but the True Shallot Seed variety Bima Brebes was the most optimal in terms of the number of bulbs and yield weight of the plants. The constraints of seed production process were the low percentage of flowering and seed formation (seed-set). Conclusion: The research results showed that the Bima shallot variety is most suitable for development and recommended in lowland areas of Nganjuk District.